2017
DOI: 10.1007/s11104-017-3239-4
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic or environmental control on the elemental and organo-chemical composition of Sphagnum mosses?

Abstract: Background and aims Plant litter chemistry is a key driver of decomposition in peatlands. This study explored the relative contributions of phylogeny and environment to litter chemistry of peat mosses (Sphagnum), the key peat-forming plants on earth. Methods Fifteen Sphagnum species, representing three taxonomic sections ACUTIFOLIA, CUSPIDATA and SPHAGNUM, were sampled across a wide range of hydro-geochemical conditions. For all species we characterised chemical composition within (i) inorganic elements, (ii) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 72 publications
0
23
1
Order By: Relevance
“…These results were clearly reflected also in the PCA, but the effects of habitat versus phylogeny are hard to fully separate. Limpens et al (2017) concluded that the composition of the dominant primary metabolites (carbohydrates) in Sphagnum is phylogenetically conserved, while the secondary metabolite composition and nutrient concentration are rather controlled by the environment. Instead, we found a strong phylogenetic control on both primary and secondary metabolites, and environmental control only on the tissue nutrient concentration.…”
Section: Phylogeny Vs Habitatmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were clearly reflected also in the PCA, but the effects of habitat versus phylogeny are hard to fully separate. Limpens et al (2017) concluded that the composition of the dominant primary metabolites (carbohydrates) in Sphagnum is phylogenetically conserved, while the secondary metabolite composition and nutrient concentration are rather controlled by the environment. Instead, we found a strong phylogenetic control on both primary and secondary metabolites, and environmental control only on the tissue nutrient concentration.…”
Section: Phylogeny Vs Habitatmentioning
confidence: 99%
“…Instead, we found a strong phylogenetic control on both primary and secondary metabolites, and environmental control only on the tissue nutrient concentration. This discrepancy may result from different analytical approaches; while this study employed more direct and quantitative measures of phenolics quantification, Limpens et al (2017) applied an indirect and less quantitative method of pyrolysate composition analysis.…”
Section: Phylogeny Vs Habitatmentioning
confidence: 99%
“…However, the only trait related to height‐above‐water‐table in linear regression models is the litter quality trait of cation exchange capacity that may indicate that the other relationships are nonlinear or which the number of taxa sampled ( N = 15) was insufficient to statistically support linear relationships. Overall, there was support for the often quoted tenet that Sphagnum species growing higher above the water table tend to have lower decomposability, lower productivity and higher litter concentrations of phenolics and pectic polysaccharides (Turetsky et al ., ; HĂĄjek et al ., ; Limpens et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Extending gene‐to‐trait relationships beyond a single species is necessary for understanding the evolution of ecosystem function in Sphagnum ‐dominated peatlands. Traits important for ecosystem function differ among species, including productivity and resource acquisition, resource allocation such as production of secondary compounds, and decomposition rates (Bengtsson et al ., ; Limpens et al ., ). Therefore, in addition to the intensive within‐species resequencing approach described earlier, the Sphagnome Project includes the sequencing of 31 individuals across 15 species representing the five major clades within Sphagnum (Fig.…”
Section: Developing Resources For a Tractable Sphagnum Model System Wmentioning
confidence: 97%